2004
DOI: 10.1051/0004-6361:20031717
|View full text |Cite
|
Sign up to set email alerts
|

The radio galaxy K-z relation: The $\mathsf{10^{12}}~$M\odot mass limit

Abstract: Abstract. The narrow K-z relation of powerful radio galaxies in the Hubble K-band diagram is often attributed to the stellar populations of massive elliptical galaxies. Because it extends over a large range of redshifts (0 < z < 4), it is difficult to estimate masses at high redshifts by taking into account galaxy evolution. In the present paper, we propose to estimate the stellar masses of galaxies using the galaxy evolution model PÉGASE. We use star formation scenarios that successfully fit faint galaxy coun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
156
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(180 citation statements)
references
References 40 publications
23
156
1
Order By: Relevance
“…This links together two known correlations, namely the correlation between spectral index and redshift (Tielens et al 1979;Blumenthal & Miley 1979) and the correlation between K-band magnitude and redshift (K − z correlation; e.g., Willott et al 2003;Rocca-Volmerange et al 2004). We remark that the correlation between spectral index and redshift is not a tight correlation; for a given spectral index there is a range of possible redshifts for a radio source (e.g., Miley & De Breuck 2008).…”
Section: Identification Fraction Of Radio Sources Versus Spectral Indexmentioning
confidence: 66%
“…This links together two known correlations, namely the correlation between spectral index and redshift (Tielens et al 1979;Blumenthal & Miley 1979) and the correlation between K-band magnitude and redshift (K − z correlation; e.g., Willott et al 2003;Rocca-Volmerange et al 2004). We remark that the correlation between spectral index and redshift is not a tight correlation; for a given spectral index there is a range of possible redshifts for a radio source (e.g., Miley & De Breuck 2008).…”
Section: Identification Fraction Of Radio Sources Versus Spectral Indexmentioning
confidence: 66%
“…One technique is based on the hypothesis that at very early times the most massive galaxies trace the highest density regions and can thus be used as "lighthouses" to pinpoint possible "protoclusters." Radio galaxies (RGs) are among the largest and most massive galaxies at z = 2-5 (M * ∼ 10 10−12 M , e.g., Pentericci et al 1997;Rocca-Volmerange et al 2004;Seymour et al 2007;Hatch et al 2009, this paper), while the most luminous high-redshift quasars (QSOs) have some of the largest black hole masses inferred (M BH ∼ 10 8−10 M , e.g. Jiang et al 2007;Kurk et al 2007).…”
Section: Introductionmentioning
confidence: 87%
“…Previous studies have shown that the most powerful radio galaxies present exceptionally high masses (e.g. De Breuck et al 2002;Rocca-Volmerange et al 2004;Seymour et al 2007). This places powerful radio galaxies at the top of the galaxy mass distribution seen in large field galaxy samples (e.g., Marchesini et al 2009;Ilbert et al 2013).…”
Section: Evolved Componentmentioning
confidence: 99%